Richness and distribution of echinoderms from northern and southern reef systems in Veracruz, Mexico. - González-Gándara, Carlos; Solís-Marín, Francisco Alonso; de la Cruz-Francisco, Vicencio; Granados-Barba, Alejandro; Salas-Pérez, José de Jesús; Argüelles-Jiménez, Jimmy; Escárcega-Quiroga, Pastor Alberto (Revista de Biología Tropical, 2015)
Echinoderms are a key element in the structure and function of their ecosystems. To study composition and distribution of echinoderms from northern (Blanquilla, Medio, Lobos and Blake) and southern (La Perla, Zapotitlan, Palo Seco and Tripie) reefs of Veracruz, Mexico, 539 visual censuses and 770 collects distributed in different habitats of each reef were done from March to December 2013 using free and SCUBA diving. To evaluate spatial differences at different scales (type reef, reef and habitat), a similarity analysis was done using Jaccard index and NMDS. 45 species of 34 genera and 26 families were recorded, including five new records for Veracruz. Ophiuroidea (15 species) and Echinoidea (13 species) showed more species. Northern reefs presented more species (40 species) than southern reefs (27 species). By locality, Lobos reef presented the greatest richness (31 species) and Tripie (7 species) the poorest. NMDS at type reef separated the three type reefs, at reef scale fringing reefs were divided from platform and submerged reefs. At habitat scale, shallow zones were separated from deep areas, Thalassia beds and reef flat from slopes and there were not differences between habitats in fringing reefs except in the sunken ship. The fauna of echinoderms associated to reefs of State of Veracruz is composed by 54 species. The type of reef and the characteristics of substrate and depth are very important to define the richness and spatial distribution of echinoderms.